The Indebtedness of the Population in Slovak Republic: An Economic Perspective - ZUZANA STOLICNA; LUCIA KLAPACOVA (Communications of International Proceedings, 2022)
In recent years, Slovak households have borrowed rapidly. The current values ​​of the debt indicators of both the private and public sectors do not reach the level of the developed economies of the Eurozone. The pace of indebtedness has started to slow down slightly in the last two years. Disruption of financial stability leads to a slowdown in economic growth. However, economic developments in recent years (before the crisis) have helped Slovak households. Economic optimism has grown in the population. The expansionary monetary policy of the European Central Bank could have significantly contributed to its willingness to borrow.
Keywords: indebtedness; debt; household; net income; financial stability.